Plan for leksikalsk dokumentasjon av moderne bokmål - Vatvedt Fjeld, Ruth (Nordiske Studier i Leksikografi, 2007)
The lexicon of the modern Norwegian bokmål standard needs a better description and documentation than what is the situation today. The article presents a plan for building a modern lexical database based on a balanced corpus of 40 million words of modern bokmål. This base should serve as a source for a traditional scientific dictionary as well as a dictionary for language technological applications.